ANALISA KREDIT MODAL KERJA DAN KREDIT INVESTASI SEKTOR INDUSTRI KECIL DAN MENENGAH (STUDI KASUS PADA PT.IKS SEBAGAI DEBITUR BANK BNI - Juliani Lisma Sari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
After the monetary crisis passed then the banking business turned from corporate sector or business sectors to the sector of small and medium enterprises (SMEs). This research uses the method of observation directly to companies and to the bank through the method of interview. The data retrieved is data that is both qualitative and quantitative about the condition of the company and the provisions of the bank. The credit analysis will be based on the 5C framework, which are: Character, Capacity, Capital, Conditions of Economy and Collateral. Outline analysis of creditworthiness is divided into three aspects. The management aspects include the analysis of the history of the company, the relationship with the bank, the legality and integrity of business management, marketing and business prospects, technical aspects inclusions the production/purchase as well as aspects of business facilities. The financial aspects of the company, including an analysis of the financial statements, the vertical and horizontal analysis of financial projections and appraisal of investment analysis by doing an evaluation over the amount of his credit needs. The credit collateral aspects which include the analysis of the legality of collateral, collateral valuation moreover analysis do guarantees. The results of this research over the creditworthiness analysis of The PT.IKS bankable enough votes. Thus, can eventually develop into a major industry with the help of Bank BNI has become a loyal business partner.